Estimation of the incidence of occupational diseases in colombia, 1985-2000 (2003)
Objectives: The occurrence of labor related diseases in Colombia is unknown. The objective of this study was to estimate the incidence of occupational disease in Colombia in the period 1985-2000. Methods: The annual incidence was estimated with the methodology recommended by Leigh et al. based upon the population estimates of the National Administrative Statistics Department (DANE). Results:The results showed an increase in the incidence of occupational diseases from 68 063 cases in 1985 to 101 645 in 2000. Discussion: The economic losses caused to the social security health system by underreporting of occupational diseases are estimated.